2013
DOI: 10.1016/j.mycmed.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive functional portrait of two heat shock factor-type transcriptional regulators involved in Candida albicans morphogenesis and virulence

Abstract: Sfl1p and Sfl2p are two homologous heat shock factor-type transcriptional regulators that antagonistically control morphogenesis in Candida albicans, while being required for full pathogenesis and virulence. To understand how Sfl1p and Sfl2p exert their function, we combined genome-wide location and expression analyses to reveal their transcriptional targets in vivo together with the associated changes of the C. albicans transcriptome. We show that Sfl1p and Sfl2p bind to the promoter of at least 113 common ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
(158 reference statements)
1
4
0
Order By: Relevance
“…In fact, we found that filamentous cells were produced by the efg1/efg1 mutant but the double cph1/cph1 efg1/efg1 mutant was extremely defective for filamentation. Consistent with this view is report of Znaidi et al [37] that Efg1 is not required for filamentation during tissue invasion. Based on previous data [2,38] we selected colorectal carcinoma (Caco-2) to quantify C. albicans cells and to characteristic of morphologies produced in contact with cells surface during adherence assay as well as to demonstrate whether the expression of SAP4 gene as well as EFG1 or CPH1 are responsible for adhesion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In fact, we found that filamentous cells were produced by the efg1/efg1 mutant but the double cph1/cph1 efg1/efg1 mutant was extremely defective for filamentation. Consistent with this view is report of Znaidi et al [37] that Efg1 is not required for filamentation during tissue invasion. Based on previous data [2,38] we selected colorectal carcinoma (Caco-2) to quantify C. albicans cells and to characteristic of morphologies produced in contact with cells surface during adherence assay as well as to demonstrate whether the expression of SAP4 gene as well as EFG1 or CPH1 are responsible for adhesion.…”
Section: Discussionsupporting
confidence: 88%
“…Lo et al [5] and Znaidi et al [37] showed that strains lacking Efg1 or/ and Cph1 are defective in efficient hyphae formation and the cph1/cph1 efg1/efg1 double mutant is unable to fully undergo morphogenesis even under hyphae inducing conditions. Our previous data acquired in laboratory culture conditions [10] indicated that the cph1/cph1 strain forms true hyphae normally (even though very rarely) in comparison to efg1/efg1 as well as cph1/cph1 efg1/efg1 fully defective in true hyphae formation under human serum influence.…”
Section: Discussionmentioning
confidence: 99%
“…Specific repression of SFL2 in C. albicans was identified by Spiering et al (2010). SFL2 is a major regulator of morphogenesis in C. albicans and acts together with a homolog SFL1 to regulate expression of hyphal-and yeast-specific genes (Znaidi et al 2013).…”
Section: Post-wgd Speciesmentioning
confidence: 99%
“…39,40 Christophe D'Enfert from the Institute Pasteur in Paris, France, gave an update on regulatory networks of C. albicans morphogenesis, focusing on heat shock responsive transcription factors that play apparently antagonistic regulatory roles in hyphae formation despite binding to overlapping regions of target gene promoters; among these, a gene product essential for chlamydospore formation could be identified. 41 Furthermore, the function of a heat shock factor type DNA binding protein as master regulator for transcriptional regulators of morphology was highlighted. Finally in this session, Stephanie Diezmann from Bath, UK, shared her findings about the Hsp90 heat shock protein of C. albicans and how it affects fungal genome ploidy as well as stress responses.…”
Section: A Holistic View On Infection -Systems Biology (Session 3)mentioning
confidence: 99%
“…Di Pietro (S) 31,32 Fungal spore components determine the interaction with immune cells A. Brakhage (S) 38 Regulatory networks of C. albicans morphogenesis are complex C. D'Enfert (S) 41 Experimental evolution reveals unexpected factors of fungal virulence S. Brunke (Y) 75,76 Candida albicans produces a toxic surprise: Candidalysin J. Naglik (S) 56 Coprinopsis cinerea produces potent fungal defense effectors M. K€ unzler (S) [59][60][61] The fungal cell wall acts as immunological & drug target N. Gow (S) 70 Copper detoxification supports A. fumigatus virulence N. Osherov (Po) 77 Note. a P: plenary lecture, S: session talk, Y: young researcher presentation, Po: poster plant pathogenic fungi and might reveal natural products that are active in either host, be it plant or human.…”
Section: Take Home Message Presenter a Referencementioning
confidence: 99%